Lipid-polycaprolactone Core-shell Hybrid Nanoparticles for Controlled Delivery of Nateglinide (Asian Journal of Pharmaceutics (AJP), 2021)
Objective: Lipid-polymer hybrid nanoparticles (LPHNPs) combine the biomimetic advantages of lipids and thestructural benefits of polymers. The aim of the present study is the development of core shell LPHNPs encapsulatinga model lipophilic drug nateglinide and perceived its controlled delivery. Materials and Methods: LPHNPswere prepared by single emulsion solvent evaporation method using polycaprolactone as polymer and glycerylmonostearate, palmitic acid, and lauric acid as lipid. The formulations were characterized in terms of particlesize, zeta potential, drug entrapment efficiency, drug loading (DL), surface morphology, in vitro drug release,and release kinetics studies. Results: Dynamic light scattering analysis demonstrated the smaller particle sizeof LPHNPs (380.2 ± 3.5–544.7 ± 2.8 nm) as compared to polycaprolactone polymeric NPs (PNPs) (647.1 ±1.9–675.8 ± 3.7 nm). Transmission electron microscopy images of LPNPs and PNPs demonstrate that they arespherical in shape. The entrapment efficiencies (84.9 ± 0.1–87.76 ± 0.23%) and DL capacity (4.63 ± 0.01–8.18± 0.09%) of LPHNPs were higher than PNPs (72.5 ± 0.1% and 2.05 ± 0.005%). The higher colloidal stability ofLPHNPs was confirmed by their zeta potential value at -12.5 ± 2.1––33.4 ± 0.2 mv as compared to zeta potentialof PNPs (–8.71 ± 0.3–9.60 ± 0.1 mv). The LPHNPs displayed a biphasic drug release pattern with an initial burstrelease, followed by controlled release. The LPHNPs demonstrated the slower drug release (60–70% at 24 h) thanthat from PNPs (90% at 24 h). Conclusion: The results suggest the controlled release behavior of nateglinidefrom the developed lipid-polymer core shell hybrid NPs. The developed nanocarriers hold the great promise forcontrolled delivery of both the lipophilic and hydrophilic drugs to improve their pharmacokinetics.